Major structural elements and petrophysical properties of the miocene section, â€œXYZ Fieldâ€, western shallow Offshore Depobelt, Niger Delta - M.A, Ajibade; Adekola, Ajibade; Olowokere, M.T. (International Journal of Advanced Geosciences, 2019)
R1, R2, R3, and F. reservoir units were identified in the XYZ Field. The reservoirs are within the Oil proven fault block and F reservoir is located on the footwall structure of the second synthetic fault with similar structural characteristics. The faulting in the XYZ field resulted in a downward movement of the XYZ Discovery relative to the XYZ prospects. The structural development process of the field was a syn-sedimentary. This explains why the XYZ-1 penetration in the footwall of the synthetic found oil-in F sand. However, petrophysical results show that the reservoirs of interests have good petrophysical properties with minimum porosity of 0.1 and maximum water saturation of 0.7. The discoveries by the XYZ-1 well prove the existence of a working hydrocarbon source and charge system. However the distribution pattern of the discovered hydrocarbons is not yet understood.Â Â